One-pot resource-efficient synthesis of SnSb powders for composite anodes in sodium-ion batteries - Tan, Deming; Chen, Peng; Wang, Gang; Chen, Guangbo; Pietsch, Tobias; Brunner, Eike; Doert, Thomas; Ruck, Michael (RSC Advances, 2020)
SnSb alloy, which can be used as an anode in a sodium-ion cell, was synthesized following a resource-efficient route at low temperature. This one-pot approach greatly reduces the energy consumption and maximizes the efficient use of raw materials. The reaction of elemental tin and antimony in the ionic liquid (IL) trihexyltetradecylphosphonium chloride ([P66614]Cl) at 200 °C led to a microcrystalline powder of single-phase SnSb within 10 h with very high yield (95%). Liquid-state nuclear magnetic resonance spectroscopy revealed that the IL remains essentially stable during the reaction. It was recovered almost quantitatively by distilling off the organic solvent used for product separation. Composites of SnSb powder and carbon nanotubes (CNTs) were fabricated by a simple ball milling process. Electrochemical measurements demonstrate that the Na‖SnSb/CNTs cell retains close to 100% of its initial capacity after 50 cycles at a current of 50 mA g−1, which is much better than the Na‖SnSb cell. The greatly increased capacity retainability can be attributed to the conductive network formed by CNTs inside the SnSb/CNTs electrode, providing 3D effective and fast electronic pathways during sodium intercalation and de-intercalation.
CRIS-Team Scopus Importer:2022-04-14